Bamboo Crosswind Barrier - kamal, Muhammad afiq; Abdul Rauf, Mohammad Zahir; Mohd Rashidan, Muhammad Akma; Sanik, Mohd Erwan (Multidisciplinary Applied Research and Innovation, 2022)
Crosswind is one of the contributing factors of road accidents along highways. The high-speed wind that passes through or across the highway area is causing the moving vehicles to experience a reluctant change in driving direction that may contribute to a single-vehicle collision. This study tends to explore the use of bamboo as an alternative to replace the existing wind barriers to reduce the risk of crosswinds effect along the highways and to produce a physical model of bamboo as crosswind barrier. This study includes reviews of the past research projects related to the problem of crosswind in obtaining accurate and authentic information and facts. Interview with bamboo expert was also carried out to obtain more information about bamboo. The bamboo that has been considered as the most suitable for crosswind barrier is Oldhamii bamboo. A bamboo crosswind barrier model was produced to represent the actual situation of the barrier on the highway. This study has proven that bamboo can become an effective alternative to the existing crosswind barrier since the bamboo has many advantages in countering the crosswind problems.